Peripheral Blood Film Patterns in Thalassemia and Hemoglobinopathy Carrier (Bangladesh Journal of Medical Biochemistry, 2024)
Thalassemia and hemoglobinopthies are the commonest genetic disorders of hemoglobin. The disease has autosomal recessive pattern of inheritance. Screening of thalassemia and hemoglobinopathy carriers is a burning issue to prevent new cases. Thalassemia and hemoglobinopathies can be prevented by genetic testing followed by genetic counseling, if we can detect carriers of thalassemia or hemoglobinopathies by an easy method. The objective of this study was to see the peripheral blood film pattern among the carriers of thalassemia and hemoglobinopathies. It was a cross-sectional study conducted from September 2015 to November 2015. A total of 437 random specimens were collected from three tribal groups. Two mL of venous blood were collected in EDTA tube. Hemoglobin variants were studied by HPLC method using Variant Hemoglobin Testing System (Variant II Beta Thalassemia Short Program). Statistical analysis was carried out using SPSS statistical package (version 23.0). Data were analyzed by frequency distribution. In this study, total 437 respondents were examined for blood test. Male to female ratio was 1:1. The study included cases from 2 years to 82 years where mean age was 18.3±12.0 years. In clinical analysis, Hb ranged from 8.5 to 19.0 gm/dL and 187 cases were found normochromic, 110 cases anisochromic 140 cases hypochromic. Among them, 38.2% were normal individuals, Hb E Trait were 34.8%, Hemoglobin E disease were 21.7% and Beta Thalassemia trait were 5.3%.Peripheral blood film and hemoglobin status may give an idea about thalassaemia and hemoglbinopathy trait or carrier. In the suspected cases, High Performance Liquid Chromatography (HPLC) may be done to confirm the diagnosis.Bangladesh J Med Biochem 2019; 12(2): 23-30